A qualitative analysis of the experience of gambling harm and accessing support among United Kingdom Armed Forces personnel - Hannah Champion; Blair Biggar; Matthew Jones; Justyn Larcombe; Matt Fossey; Simon Dymond (Discover Psychology)
Abstract Background Military personnel (both currently serving and veterans) are vulnerable to harm from gambling, yet many are reluctant to seek help. The aims of this study were to explore the lived experience of gambling and gambling harm in currently serving members of the UK Armed Forces and to seek to improve military-specific gambling harm information and support. Methods Semi-structured interviews were undertaken with self-selected currently serving personnel from the UK Armed Forces. Interview questions focus on lived experience of gambling harm, motivators and triggers around gambling, and awareness of gambling information and support. Results Thematic analysis identified four main themes: (1) sociocultural pathways to gambling harm; (2) influencing factors unique to military life; (3) obstacles to early intervention and support; and (4) facilitators of help and support. Conclusions Findings showed that the nature and extent of gambling harm within the UK Armed Forces may not be fully acknowledged, and that currently serving personnel face barriers accessing safer gambling information and support. Specifically, there was a lack of education around the nature of gambling harm, identifying it, how to go about seeking help, and from whom. The normalisation of potentially harmful behaviour, stigmatising attitudes, and concerns around anonymity serve as further barriers to help-seeking. There is a need to raise awareness, reduce stigma, and enhance support for gambling harm within the UK Armed Forces.